2020
DOI: 10.21098/bemp.v23i4.1363
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus Among Employment, Productivity and Trade Openness: Evidence From Brics and Indonesia

Abstract: This paper investigates the nexus among employment, labor productivity and trade openness in Brazil, Russia, India, China, South Africa (BRICS), and Indonesia using annual data (1991–2018). The results suggest a long-run relationship among the variables but only in the agricultural sector of these economies. We also find a unidirectional causality running from employment to productivity in only the agricultural sector. Similarly, trade openness also Granger causes employment. Our final result indicates that tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Also, using fixed effects and two-stage least squares estimation methods for a panel data of 38 SSA countries for the period of 1991–2010, Wamboye and Seguino (2012) found that trade liberalization has gendered effects and the direction depends on the structure of the economy. Furthermore, Rath and Ridhwan (2020) used annual data from 1991 to 2018 to examine the nexus among trade, productivity and employment among six emerging countries (Brazil, Russia, India, China, South Africa and Indonesia). The authors found evidence that trade openness granger causes employment in those countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, using fixed effects and two-stage least squares estimation methods for a panel data of 38 SSA countries for the period of 1991–2010, Wamboye and Seguino (2012) found that trade liberalization has gendered effects and the direction depends on the structure of the economy. Furthermore, Rath and Ridhwan (2020) used annual data from 1991 to 2018 to examine the nexus among trade, productivity and employment among six emerging countries (Brazil, Russia, India, China, South Africa and Indonesia). The authors found evidence that trade openness granger causes employment in those countries.…”
Section: Literature Reviewmentioning
confidence: 99%